Post Mastectomy Pain Syndrome (PMPS) Incident Profile at Ibnu Sina Hospital Makassar in May–August 2024 - Djibran, Moh. Rizqullah; Dwimartyono, Fendy; Syahruddin, Febie Irsandy; Hasbi, Berry Erida; Harahap, Muh. Wirawan (Faculty of Medicine, Universitas Tadulako, 2025)
Background: Post-Mastectomy Pain Syndrome (PMPS) is a chronic neuropathic pain lasting over three months after mastectomy, often affecting the chest, axilla, or arm, yet data on its prevalence in Eastern Indonesia remain scarce. Objective: To describe the characteristics and impact of PMPS among post-mastectomy patients at Ibnu Sina Hospital. Methods: A descriptive observational study was conducted involving 30 post-mastectomy patients diagnosed with PMPS, using univariate analysis with SPSS 25.0 to assess pain characteristics and quality-of-life effects, with neuropathic pain defined as a score >/ 4 on the Neuropathic Pain Scale. Results: The majority of patients (76.7%) experienced chronic pain localized mainly to the anterior chest and axilla, often radiating to the upper arm. About 70.0% reported significant interference with daily activities, sleep disturbance, and psychological distress, while 60.0% experienced pain exacerbation during shoulder movement. Neuropathic characteristics such as burning and tingling sensations were frequently reported, with moderate to severe pain intensity noted in over half of the participants. These findings indicate that PMPS substantially compromises patients’ physical function and emotional well-being during postoperative recovery. Conclusion: PMPS prevalence is high and markedly affects quality of life, necessitating early screening and multidisciplinary pain management in post-mastectomy care.